Jamaica : Ninth Review Under the Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria-Press Release; Staff Report; and Statement by the Executive Director for Jamaica. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Jamaica's Ninth Review Under the Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria (PC). Macroeconomic indicators are improving, but growth remains sluggish. Growth has been revised down to 1.4 percent for FY2015/16 as drought continues to impede agricultural growth for a second year in a row. The program is on track. All the quantitative PCs were met, and structural reforms are broadly on schedule. The transition of the retail repo contracts to a trust-based framework has been completed. Based on continued strong program implementation and the authorities' policy commitments, the IMF staff recommends completion of the ninth review.